First report of a multidrug-resistant Salmonella enterica Serovar Infantis carrying pESI megaplasmid isolated from marine shrimp in India. (December 2022) - Stephen, Jerusha; Lekshmi, Manjusha; Nayak, Binaya Bhusan; Kumar, Sanath H.
Highlights: Salmonella. enterica serovar infantis strain JS5 carrying a megaplasmid (pESI) was isolated from shrimp. A 285 kb plasmid with IncFIB9 replicon showed 99.21% nucleotide similarity with pESI plasmid. Multiple antibiotic resistance genes tet (A), dfrA14, aadA, qacEdelta1, sul1 were encoded on the plasmid. Abstract: Background: Non-typhoidal Salmonella enterica (NTS) in seafood is an important human health concern. An emerging strain of NTS serovar Infantis carrying a megaplasmid pESI and resistant to multipe drugs has been responsible for frequent food-borne human infections worldwide. Methods: S. enterica strain JS5 was isolated from a sample of shrimp from the retail market on XLD agar after enrichment in the RV medium. The genomic DNA was isolated and sequenced using the Illumina platform. The draft whole genome sequence of Salmonella Infantis JS5 revealed the presence of a plasmid. Results: The genome size was 4, 977, 731 bp with 4663 open reading frames. The bacterium harboured a megaplasmid similar to the pESI plasmid reported in the emerging S . Infantis. The 285 kb plasmid contained the characteristic genes of the pESI plasmids, such as the mercury operon, yersiniabactin siderophore operon, fimbriae, toxin-antitoxin systems and the hypothetical protein backbone. The antibiotic resistance genes tet (A), dfrA14, aadA, qacEdelta1, and sul1 were detected. To the best of our knowledge, this is the first report on pESI plasmid carrying S. Infantis from India.